Toxic megacolon - Leppkes, M.; Ganslmayer, M.; Strauss, R.; Neurath, Markus (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2015)
Toxic megacolon constitutes a feared, life-threatening complication of severe intestinal inflammation and is a challenge for interdisciplinary medical care.Specific aspects of conservative treatment based on current scientific evidence derived from guidelines, qualified reviews, and scientific studies are presented, which provide a rational approach and maximize therapeutic success.This work is based on a selective literature review and the authors' experience of many years in gastroenterology and intensive care.Toxic megacolon requires a rapid interdisciplinary assessment. Depending on the underlying etiology, an individual treatment concept needs to be developed. If an infectious or inflammatory cause is probable, a conservative approach can reduce perioperative morbidity and mortality. A step-wise approach with controlled reevaluations of the response to therapy after 72 h and 7 days avoids uncontrolled delay of surgical options further ensuring patient safety.Despite a decreasing incidence of toxic megacolon, it remains an interdisciplinary therapeutic challenge.
EVALuna2:2018